2017
DOI: 10.1002/jcb.26402
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fibroblast growth factor 8 (FGF8) in chicken embryonic stem cells differentiation into spermatogonial stem cells

Abstract: Fibroblast growth factors (FGFs) are essential in regulating the formation of spermatogonial stem cells (SSCs). Here, we explored the effect of FGF8 on chicken SSCs formation by knockdown or overexpression of FGF8 in chicken embryonic stem cells (ESCs) both in vitro and in vivo. Our results showed that knockdown of FGF8 could facilitate the differentiation of ESCs into SSCs, overexpression of FGF8 could promote PGCs self-renewal, inhibit SSCs formation. This study further revealed the positive correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…In this study, we noted that MAPK1 expression changes caused corresponding changes in the ERK and WNT signaling pathways, suggesting that LncPGCAT‐1 and gga‐mir‐1591 regulate MAPK signaling via MAPK1 (Figure 5e). Furthermore, in a previous study, we demonstrated that activated MAPK (upregulated ERK) promotes PGC formation (M. Wang et al, 2018). To further demonstrate the relationship between LncPGCAT‐1 , gga‐mir‐1591, MAPK1 , and MAPK signals, we performed a rescue experiment (Figure 5b–d).…”
Section: Resultsmentioning
confidence: 71%
“…In this study, we noted that MAPK1 expression changes caused corresponding changes in the ERK and WNT signaling pathways, suggesting that LncPGCAT‐1 and gga‐mir‐1591 regulate MAPK signaling via MAPK1 (Figure 5e). Furthermore, in a previous study, we demonstrated that activated MAPK (upregulated ERK) promotes PGC formation (M. Wang et al, 2018). To further demonstrate the relationship between LncPGCAT‐1 , gga‐mir‐1591, MAPK1 , and MAPK signals, we performed a rescue experiment (Figure 5b–d).…”
Section: Resultsmentioning
confidence: 71%
“…FGFs play an important role in various developmental processes of chicken embryos [16,17] and in embryonic stem cell differentiation and primordial germ cells through the activation of MAPK/ERK signaling pathways [3,14]. Several chicken FGFs have been identified and functionally characterized, including FGF1 [2], FGF2, FGF4 [12,13], FGF8 [14], FGF12-13 [15],…”
Section: Discussionmentioning
confidence: 99%
“…Several FGFs have been isolated and well-characterized in chickens, including FGF1 [2], FGF2, FGF4 [12,13], FGF8 [14], FGF12-13 [15], and FGF19 [16]. These genes play important roles in various developmental processes of chicken embryos [16,17] and in embryonic stem cell differentiation and primordial germ cells through the activation of MAPK/ERK signaling pathways [3,14]. However, the FGF gene family in chickens still lacks identification and information on genome structure, physicochemical properties, and phylogenetic relationships.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a series of paracrine molecules excreted by MSCs have been discovered, including cytokines, growth factors, exosomes, and non-coding RNAs. Many of them are involved in the regulation of MAPK/ERK signaling pathway (Table 3) [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. Of these, ERBB4, Spred1, miR-125b, HOTAIRM1-1, and miR-133a are negative regulators, while HIF-2α, IGF-1, TGF-β3, bFGF, VEGF, BDNF, METTL1, FGF8, IGF-1, SCGF-beta, HGF, MCP-1, miR-126, SMSCs-126-Exos, ApoE, IL-8, and IL-6 are positive regulators.…”
Section: Discussionmentioning
confidence: 99%